Ex vivo human skin and SZ95 sebocytes exhibit a homoeostatic interaction in a novel coculture contact model. Issue 7 (4th May 2015) - Nikolakis, Georgios; Seltmann, Holger; Hossini, Amir M.; Makrantonaki, Evgenia; Knolle, Jürgen; Zouboulis, Christos C.
Abstract The sebaceous gland displays key functions of the human skin, such as hormone synthesis in situ, antimicrobial activity and participation to inflammatory responses. Consequently, there is an emerging need of advanced in vitro models to study complex interactions between the sebaceous gland and the other skin compartments. Despite the evolution of both full‐skin organ culture and reconstructed three‐dimensional skin models, no satisfactory solutions have been provided for the integration of sebaceous glands and/or sebaceous gland cells in those models, probably due to their problematic maintenance both in vitro and ex vivo. We have developed a coculture model of explant skin in direct contact with immortalized SZ95 sebocytes, which resulted in overall improved structural integrity of the epidermis, higher percentage of proliferating basal epidermal cells and reduced apoptosis of differentiating keratinocytes after 6 days, as detected by Ki67 and TUNEL staining, respectively. Furthermore SZ95 sebocytes exhibited morphological and biochemical signs of normal differentiation and lipid accumulation, while interleukin‐6 expression in the supernatant of the cocultures was decreased in comparison with the control. The data provide evidence of a beneficial interaction between sebocytes and skin explants and provide the rationale for their integration in future three‐dimensional skin models.